2020
DOI: 10.34172/jcs.2020.023
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Job Burnout: A Hybrid Concept Analysis

Abstract: Introduction: Job burnout can significantly affect nurses' physical and mental health and the quality of the care services they provide. Yet, there is no clear definition for job burnout in nursing. This study aimed to analyze the concept of nurses' occupational burnout. Methods: This concept analysis was conducted, using the three-phase hybrid model. In the theoretical phase, online databases, namely Iranmedex, Scientific Information Database (SID), Science Direct, MagIran, ProQuest, Web of Sciences, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
(85 reference statements)
0
10
0
2
Order By: Relevance
“…Nonetheless, the decision tree shows that over‐identification also has a significant influence on BO, which is consistent with over‐identification being conceptualized as the opposite of mindfulness in the construction of the scale used to measure self‐compassion in our study (Neff, 2003). This negative relationship between mindfulness and BO is to be expected, as mindfulness is a state of balance in which individuals are aware of their thoughts and feelings without judging them and without running away from them (Neff, 2003), whereas BO is characterized by, among other things, a lack of professional fulfilment resulting in low self‐esteem and negative assessments of one's own work (Nabizadeh‐Gharghozar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the decision tree shows that over‐identification also has a significant influence on BO, which is consistent with over‐identification being conceptualized as the opposite of mindfulness in the construction of the scale used to measure self‐compassion in our study (Neff, 2003). This negative relationship between mindfulness and BO is to be expected, as mindfulness is a state of balance in which individuals are aware of their thoughts and feelings without judging them and without running away from them (Neff, 2003), whereas BO is characterized by, among other things, a lack of professional fulfilment resulting in low self‐esteem and negative assessments of one's own work (Nabizadeh‐Gharghozar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Burnout, a syndrome of emotional exhaustion and cynicism, often happens to individuals who are engaged in some kinds of "people-work" (1), and it is often measured using the Maslach Burnout Inventory with 3 dimensions (emotional exhaustion, depersonalization and personal accomplishment) (2). Nurses are more likely to have job burnout, since they work in different conditions of clinical settings and are close related with patient care, which puts high physical and psychological pressure on nurses (3). Literatures showed insomnia and burnout were closely related with each other in nurses (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from team cooperation, the job resources did not significantly reduce the risk for emotional exhaustion in our sample. But other studies have shown the important role of social support from colleagues and supervisors for nurses' mental health (Nabizadeh‐Gharghozar et al, 2020; Weigl et al, 2016). Other job demands that have not been presented may also increase the risk of emotional exhaustion and even burnout.…”
Section: Discussionmentioning
confidence: 96%